(untitled) (Heritage, 2022)
The paper presents the results of research conducted on the population of refugees and internally displaced persons in Kosovo and Metohija, stationed in four collective centers of the second northernmost municipality of Zubin Potok (Gazivode, Velji Breg, Jagnjenica and Donje Varage). The survey was conducted using a questionnaire method with a survey technique using the SILC survey (Income and Living Conditions Survey) on a representative sample. The goal was to collect data from a population that is mostly excluded from social surveys and census surveys, bearing in mind the fact that the aforementioned collective centers are located in Kosovo and Metohija, where official republican surveys of marginal groups have not been conducted for more than two decades. In accordance with the scope of work, the text shows only some indicators that showed the deprivation of the population of refugees and internally displaced persons